Interpersonal Movement Synchrony Responds to High- and Low-Level Conversational Constraints - Paxton, Alexandra; Dale, Rick (Frontiers in Psychology, 2017)
Much work on communication and joint action conceptualizes interaction as a dynamical system. Under this view, dynamic properties of interaction should be shaped by the context in which the interaction is taking place. Here we explore interpersonal movement coordination or synchrony---the degree to which individuals move in similar ways over time---as one such context-sensitive property. Studies of coordination have typically investigated how these dynamics are influenced by either high-level constraints (i.e., slow-changing factors) or low-level constraints (i.e., fast-changing factors like movement). Focusing on nonverbal communication behaviors during naturalistic conversation, we analyzed how interacting participants' head movement dynamics were shaped simultaneously by high-level constraints (i.e., conversation type; friendly conversations or arguments) and low-level constraints (i.e., perceptual stimuli; non-informative visual stimuli vs. informative visual stimuli). We found that high- and low-level constraints interacted non-additively to affect interpersonal movement dynamics, highlighting the context sensitivity of interaction and supporting the view of joint action as a complex adaptive system.